Модель дослідження окремих методів контролю ресурсів доступу до послуг multi play - Волокітіна, О. І. (ХНУРЕ, 2020)
New technologies spread m the world market and provide an opportunity to create united information society where the geographical boundaries lose its relevance as an economical factor. The work includes the program, developed using the Java programming language to illustrate the packet traffic movement in the network under investigation and to calculate its parameters. This research have shown that the method of using classes is more effective because the C-clients get the proper speed of Internet.